2005
DOI: 10.1016/j.ymthe.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of aspartoacylase activity in CNS neurons does not ameliorate motor deficits and demyelination in a model of Canavan disease

Abstract: Canavan disease is an early onset leukodystrophy associated with psychomotor retardation, seizures, and premature death. This disorder is caused by mutations in the gene encoding the enzyme aspartoacylase (ASPA). Normally, ASPA is enriched in oligodendrocytes and ASPA deficiency results in elevated levels of its substrate molecule, N-acetylaspartate (NAA), brain edema, and dysmyelination. Using adeno-associated virus, we permanently expressed ASPA in CNS neurons of the tremor rat, a genetic model of Canavan di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
6
41
0
1
Order By: Relevance
“…In one of these gene transfer studies in Tremor rats, NAA levels were reduced, and seizure activity was diminished, but brain vacuolation and dysmyelination were unaffected, suggesting that these pathological features of the disease are not mediated by excessive NAA concentrations (Klugmann et al, 2005). More importantly, no motor improvements were observed in the Tremor rats after gene transfer.…”
Section: Gene Transfer Therapy For Canavan Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…In one of these gene transfer studies in Tremor rats, NAA levels were reduced, and seizure activity was diminished, but brain vacuolation and dysmyelination were unaffected, suggesting that these pathological features of the disease are not mediated by excessive NAA concentrations (Klugmann et al, 2005). More importantly, no motor improvements were observed in the Tremor rats after gene transfer.…”
Section: Gene Transfer Therapy For Canavan Diseasementioning
confidence: 96%
“…The most recent adenoviral gene transfer studies employed improved gene transfer technology using the recombinant adeno-associated virus serotype 2 vector (AAV-2) (Klugmann et al, 2005;McPhee et al, 2005). In one of these gene transfer studies in Tremor rats, NAA levels were reduced, and seizure activity was diminished, but brain vacuolation and dysmyelination were unaffected, suggesting that these pathological features of the disease are not mediated by excessive NAA concentrations (Klugmann et al, 2005).…”
Section: Gene Transfer Therapy For Canavan Diseasementioning
confidence: 99%
“…Thus, delivery of the ASPA gene by viral vectors to the brain ameliorated tonic convulsions and other behavioral defects in two independent studies [111,148]. However, a similar study using adeno associated virus-mediated overexpression of ASPA reported rescue of the seizure phenotype, but no effects on hypomyelination and motor defects, suggesting that this gene therapy approach reduced neuronal hyperexcitation, but not oligodendrocyte dysfunction [80].…”
Section: Gene Therapies -Rationalementioning
confidence: 96%
“…However, it must be noted that in some cases the observed decrease in NAA and spongiform pathology is transient , while in others the effects are limited within a confined area surrounding the region of intracerebral injection (Leone et al, 2000;. Improved motor function was noted in certain cases (Ahmed et al, 2013;Leone et al, 2012;McPhee et al, 2005), but not in all (Klugmann et al, 2005). Moreover, where motor defects were improved, they did not disappear altogether and were shown in a longitudinal study to relapse later in life (Ahmed et al, 2013).…”
Section: Therapeutic Approaches To CDmentioning
confidence: 98%
“…This approach has seen a degree of success in improving the major disease symptoms; however, progress is still to be made. The use of liposome encapsulated plasmids and adeno-associated viruses as vectors to insert the ASPA gene into CD mice, tremor mice and human CD subjects has resulted in enhanced ASPA production and activity and, in some cases, reduced CNS NAA levels and improved spongiform degeneration (Ahmed et al, 2013;Klugmann et al, 2005;Leone et al, 2000;Leone et al, 2012;McPhee et al, 2005). However, it must be noted that in some cases the observed decrease in NAA and spongiform pathology is transient , while in others the effects are limited within a confined area surrounding the region of intracerebral injection (Leone et al, 2000;.…”
Section: Therapeutic Approaches To CDmentioning
confidence: 99%